Barriers and facilitators for healthcare access among immigrants in Japan: a mixed methods systematic review and meta-synthesisResearch in context - Yu Par Khin; Floret Maame Owusu; Nobutoshi Nawa; Pamela J. Surkan; Takeo Fujiwara (The Lancet Regional Health. Western Pacific)
Summary: Background: While Japan provides universal healthcare, immigrants may experience hampered access to healthcare. A comprehensive review of immigrant healthcare access is also lacking. This systematic review aims to examine barriers and facilitators of healthcare access among immigrants in Japan. Methods: We searched for literature published in English and Japanese until January 9, 2024. Studies were included if they assessed factors influencing any stage of immigrants’ healthcare access, such as perceiving needs, seeking, reaching, utilizing healthcare and the consequences of healthcare, as defined by the Levesque framework. We performed a thematic analysis to further identify categories (PROSPERO: CRD42023418554). Findings: After screening 2791 articles, we identified 67 studies (40 quantitative, 23 qualitative, 4 mixed methods) meeting eligibility criteria. Limited healthcare information led immigrants to seek alternative information sources and affected immigrants' perceived healthcare needs. Longer duration of stay improved access to healthcare information. Cultural and healthcare system differences affected healthcare seeking. Reaching and utilizing healthcare were hindered by heavy workloads, undocumented status, financial hardship, and limited insurance but were facilitated by support from family and friends. The healthcare system was often insufficient to support immigrants’ language and cultural needs leading to dissatisfaction and poor compliance. Interpretation: Findings highlight the critical importance of a multidimensional approach to support immigrants in Japan, ranging from improving healthcare information access to creating immigrant-friendly health systems. More research is needed on the healthcare access among vulnerable immigrants, such as undocumented and low-skilled labor immigrants and children. Funding: No specific funding source supported this study.